Cycle of the sexual segment of the kidney: histological insights into the role of the urinary tract in the reproduction of male Notomabuya frenata (Squamata: Scincidae) - Migliore, Serena N.; Ramalho, Renan A. [UNESP]; Araújo, Gabrieli S. [UNESP]; Almeida-Santos, Selma M. [UNESP] (Elsevier, 2024)
The kidneys of male Squamata have an important reproductive function as some portions of the nephron may undergo hypertrophy, characterizing the sexual segment of the kidney (SSK). Although its function is still not completely understood, it is believed that the secretions produced by the SSK may act in the maintenance of spermatozoa. In this study, we investigated the reproductive biology of males of Notomabuya frenata based on the seasonal variation of the SSK. We performed macroscopic and microscopic evaluations of the male reproductive tract of museum specimens to characterize the SSK cycle. The nephron portion in which hypertrophy was observed was the collecting duct with secretory granules accumulation in the apical portion. SSK hypertrophy was observed in all seasons, with the tubule diameter in autumn differing from spring and the epithelium height showing no variation. Alcian Blue reacted positively to acid mucopolysaccharides in all seasons. Periodic acid–Schiff's reacted positively to neutral mucopolysaccharides in all seasons, except autumn. Both stains reacted only in the collecting duct. In addition, spermatozoa were found in the lumen of the SSK of one specimen examined. Cycle of the SSK varied seasonally as does the chemical composition of the secretions produced by the collecting duct. The reflux of spermatozoa into SSK may indicate that (1) these secretions act in sperm maintenance, and (2) possibly there is communication between the seminal and urinary ducts.
Keywords: Androgen-dependent structure; Atlantic Forest; Cerrado; Mabuynae; Reproductive biology